Low AMH levels as a marker of reduced ovarian reserve in young women affected by Down's syndrome. Issue 11 (November 2016) - Romualdi, Daniela; Proto, Caterina; De Cicco, Simona; Immediata, Valentina; Barone, Concetta; Romano, Corrado; Lanzone, Antonio
Abstract: Objective: Women with Down's syndrome (DS) experience menopause earlier than healthy women and are twice as likely to undergo premature ovarian insufficiency. Menopause accelerates cognitive decline and is associated with a twofold increased mortality risk in DS women. Nonetheless, no previous studies investigated the ovarian reserve in this population. The aim of the present study was to evaluate the circulating antimullerian hormone (AMH) levels in DS women with regular menstrual cycles, in comparison with those observed in an age-matched group of healthy women. Methods: Fourteen women with DS and 20 normo-ovulatory volunteers were enrolled in this study. A general physical examination was performed. Hormonal assays, including AMH, fasting insulin levels, and homeostatic model assessment-insulin resistance, were investigated in all participants. Results: AMH levels were significantly lower in DS women compared with controls (1.34 ± 1.11 vs 3.01 ± 1.65 ng/mL, P  < 0.01). Prolactin concentrations were in the normal range, although higher in DS women compared with controls ( P  < 0.01). After dividing the participants according to age, AMH was significantly lower in the DS group compared with controls, both below and above 30 years of age (1.77 vs 3.73 ng/mL, P  < 0.01; 0.28 vs 2.20 ng/mL, P  < 0.01, respectively). AMH was inversely correlated with age in both groups, and directly correlated with testosterone and dehydroepiandrosterone sulfate only in DS women. In the same participants, AMH showed a tendency toward a direct correlation with insulin levels ( P  = 0.055). Conclusions: AMH levels were significantly lower in DS women compared with age-matched controls. A subanalysis of data in DS participants under 30 years of age suggested an early follicular depletion related to trisomy 21.